Reading Latin American Liberating Pedagogy from an Islamic Education Perspective - Husni, Husni; Munandar, Didih Syakir (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2022)
In Latin America, liberating pedagogy is based on the concern that education has become a tool for oppression. Supporters of this educational concept believe that oppressive education should be dismantled through what is known as liberating pedagogy. The spirit of liberating pedagogy is similar to the idea of Islamic education. Both have the same spirit: freeing people from constraints and oppression. Both are interested in humanization to combat dehumanization, injustice, and oppression. This closeness in spirit stems from Islam's vision and mission of rescuing the Arab country (in particular) and humanity from slavery, oppression, inequality, injustice, and colonialism.